A bovine-specific FSH enzyme immunoassay and its application to study the role of FSH in ovarian follicle development during the postnatal period. (20th December 2018) - Lainé, A.-L.; Laclie, C.; Furlong, J.; Crowe, M. A.; Monniaux, D.
Abstract : The primary aim of this study was to develop a FSH enzyme immunoassay (EIA) for the bovine species. The newly developed EIA was validated for FSH determination in bovine plasma by comparison with an existing bovine FSH radioimmunoassay. The EIA detected bovine FSH with a high sensitivity (0.1 ng/ml). Cross-reactivity of the EIA was 0.01% with bovine LH, 51% with ovine FSH, <0.1% with porcine FSH and <0.01% with equine FSH. Using this EIA on different time series of plasma in cows, we have confirmed the presence of a FSH pre-ovulatory peak at estrus, of periodic FSH fluctuations accompanying the waves of terminal follicular development, and of FSH pulses, mainly asynchronous with LH ones, in the peri-ovulatory phase of the cycle. In a second objective, the EIA was used to assess the role of FSH in regulating the development of ovarian follicles up to the small antral stage in young calves. To answer this question, six calves were submitted to weekly blood sampling during their first 3 months of life, and FSH changes were studied concomitantly to those of anti-Müllerian hormone (AMH), a well-established endocrine marker of the ovarian population of small antral follicles in cows. In the ovaries of 3-month calves, the population of 3 to 5 mm follicles contained the highest intra-follicular AMH amounts, and the number of 3 to 5 mm follicles on ovaries was closely correlated with AMH concentrations in the plasma of calves at this age ( r s = 0.94). Before 3 months of age, only two out of six calves showed a clear postnatal FSH peak in plasma, and no correlation was found between plasma FSH and AMH concentrations. These results indicate that female calves undergo different patterns of FSH secretion and that postnatal activation of follicular growth up to the small antral stage appears independent and not directly related to circulating FSH levels.